Biological Activity Evaluation of Some New Benzenesulphonamide Derivatives - Eze, Florence Uchenna; Okoro, Uchechukwu Christopher; Ugwu, David Izuchukwu; Okafor, Sunday N. (Frontiers in Chemistry, 2019)
Bacterial resistance to antibiotics over the past few decades has become one of the most challenging problems of infectious treatment. Sulphonamides and carboxamides have shown quite a number of pharmacological properties against different types of diseases among which is microbial infection. Ten new derivatives of benzenesulphonamide bearing carboxamide functionality were synthesized and investigated for their in vivo anti-inflammatory, in vitro anti-microbial and anti-oxidant activities. The base promoted reactions of the appropriate amino acids with substituted benzenesulphonyl chlorides gave the benzene sulphonamides (3a-j) in excellent yields. Palladium mediated amidation of the benzenesulphonamides (3a-j) and butylamine gave the new carboxamides (4a-j) in excellent yield. Compounds 4a and 4c inhibited carrageenan induced rat-paw oedema at 94.69, 89.66 and 87.83 % each at 1 h, 2 h and 3 h respectively. In the antimicrobial activity, compound 4d (MIC 6.72 mg/mL) was most potent against E.coli, compound 4h (MIC 6.63 mg/mL) was the most active against S. aures, compound 4a (MIC 6.67 and 6.45 mg/mL) was most active against P. aeruginosa and S. typhi respectively, compound 4f (MIC 6.63 mg/mL) was the most active against B. subtilis, compounds 4e and 4h (MIC 6.63mg/mL) each were the most active against C. albican, while compound 4e (MIC 6.28 mg/mL) was most active against A. niger. Only compound 4e (IC50 0.3287 mg/mL) had comparable activity with Vitamin C (IC50 0.2090 mg/mL).